1972
DOI: 10.1159/000459468
|View full text |Cite
|
Sign up to set email alerts
|

Dual Control of Glucose 6-Phosphate Dehydrogenase Induction in Rat Liver by Dietary Glucose and Amino Acids

Abstract: Inhibitory effect of actinomycin D on the induction of glucose 6-phosphate dehydrogenase in rat liver by fasting and refeeding a mixture of glucose and casein was eliminated by a prior glucose feeding, which by itself caused no induction. Refeeding casein alone failed to induce the enzyme even in glucose-prefed rats. Casein could be replaced by essential and nonessential amino acids, or by either alone; thus, no specific amino acids were involved in this enzyme induction. These results suggest that the dietary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

1975
1975
1978
1978

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 12 publications
2
11
0
Order By: Relevance
“…The activity of G6PD in liver supernatant increased in both CCl4-poisoned and GC-refed rats as reported previously [16,17,23] (table I). Among other glycolytic enzymes assayed simultaneously for comparison of glucagon effect, increased activities of HK and PK-M2 by CCl4-induced liver injury and those of GK and PK-L by refeeding GC confirmed our previous results [16].…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The activity of G6PD in liver supernatant increased in both CCl4-poisoned and GC-refed rats as reported previously [16,17,23] (table I). Among other glycolytic enzymes assayed simultaneously for comparison of glucagon effect, increased activities of HK and PK-M2 by CCl4-induced liver injury and those of GK and PK-L by refeeding GC confirmed our previous results [16].…”
Section: Resultssupporting
confidence: 86%
“…The activity of glucose-6-phosphate dehydrogenase (G6PD, D-glucose-6-phosphate: NADP oxidoreductase, EC 1.1.1.49) in liver supernatant of rat has been reported to increase by carbon tetrachloride (CC14) poisoning [16,23] as well as refeeding a carbohydrate fat-free diet [8,17,19]. These increases of G6PD activity involved the same molecular species of G6PD [22], How ever, the increased incorporation of 14C-leucine into G6PD after CC14 treatment was not affected by the administration of actinomycin D at a dose sufficient to inhibit the dietary induction of this enzyme [23], suggesting the existence of different mechanisms of G6PD induction.…”
Section: Introductionmentioning
confidence: 99%
“…It is now evident that the mechanism of enzyme alteration by hepatic injury is different from that of the dietary induced change. Parabiosis experiments gave negative results for the involvement of humoral factor in CCl4-induced changes in hepatic enzyme levels [8], It has been shown that G6PD is induced by liver injury under the condition where dietary induction of this enzyme does not occur [8], and that the mechanism, involved in G6PD induction by liver injury, is a post-transcriptional dys régulation of G6PD synthesis [50] in contrast to the dietary induction of this enzyme in which both transcriptional and translational regulations are equally important [56], A similar mechanism has also been suggested for the increased activities of HK and PK-M2 in the injured liver [8]. In the liver injury the synthesis of total hepatic proteins is markedly depressed [50,57], and the inducibility of GK by glucose is abolished [2],…”
Section: Discussionmentioning
confidence: 99%
“…By means of quantitative immunochemical techniques, we have shown directly that the increase in G6PD activity is, in fact, due to an increased rate of G6PD synthesis [39,40]. Thus, the term 'induction' is used in this study to describe the increase in G6PD level in livers under conditions tested, and it most probably represents the increase in de novo synthesis of the enzyme [32].…”
Section: Introductionmentioning
confidence: 88%
“…The increase in G6PD activity can be inhibited by treatment with actinomycin D [31,31], 8-azaguanine [9,13,26], puromycin [17], ethionine [36] or cycloheximide [39], suggesting that the increased activity is due to de novo synthesis of the enzyme protein. By means of quantitative immunochemical techniques, we have shown directly that the increase in G6PD activity is, in fact, due to an increased rate of G6PD synthesis [39,40].…”
Section: Introductionmentioning
confidence: 99%